2005
DOI: 10.1097/01.brs.0000170561.25636.1c
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Multicenter Food and Drug Administration Investigational Device Exemption Study of Lumbar Total Disc Replacement With the CHARITÉ ™ Artificial Disc Versus Lumbar Fusion

Abstract: Preoperative ROM in flexion/extension was restored and maintained in patients receiving a TDR. TDR with the CHARITE artificial disc resulted in significantly better restoration of disc space height, and significantly less subsidence than anterior interbody fusion with BAK cages. Clinical outcomes and flexion/extension ROM correlated with surgical technical accuracy of CHARITE artificial disc placement. In the majority of cases, placement of the CHARITE artificial disc was ideal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(155 citation statements)
references
References 16 publications
7
144
0
1
Order By: Relevance
“…McAfee et al [34] reported an operative level ROM of 113.6% of preoperative status in TDR group at 24 months (7.4 ± 5.28), and the mean ROM in fusion group has dropped to 1.1 ± 0.87 (with 91.9% patient gaining successful lumbar fusion). In Delamarter's study [23], the result showed significantly better motility at L4-L5 for disc replacement patients (10.5°at 12 months) comparing with the fusion patients (P \ 0.05), but at L5-S1 the differences between two groups was not statistically significant at 6-month point.…”
Section: Qualitative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…McAfee et al [34] reported an operative level ROM of 113.6% of preoperative status in TDR group at 24 months (7.4 ± 5.28), and the mean ROM in fusion group has dropped to 1.1 ± 0.87 (with 91.9% patient gaining successful lumbar fusion). In Delamarter's study [23], the result showed significantly better motility at L4-L5 for disc replacement patients (10.5°at 12 months) comparing with the fusion patients (P \ 0.05), but at L5-S1 the differences between two groups was not statistically significant at 6-month point.…”
Section: Qualitative Resultsmentioning
confidence: 99%
“…These reports were based upon five independent continuous clinical randomized control trials, reporting for different follow-up periods or containing separated results. Nine reports from the five RCTs with the relevant information are eventually included involving 837 patients [2,3,9,18,20,34,36,41,48].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Other studies however continue to report TDR flexion-extension ROM values even below this suggested 2°threshold [13,17]. A recent study suggests that a threshold angle of at least 4.6°between flexion-extension radiographs must be measured before one can be certain that the ROM of the TDR is not 0 [15].…”
Section: Discussionmentioning
confidence: 97%
“…With considerable ([5°) segmental flexion-extension range of motion (ROM), TDRs have been correlated to better clinical outcomes [7], and suggested to have reduced long-term risk in the development of radiographic adjacent level degeneration [8,18]. Correct surgical placement of the TDR has been reported to be essential in achieving these improved clinical outcomes as well as flexion-extension ROM [3,17]. Accurate post-operative measurement of TDR ROM is thus important in gauging both implant performance and surgical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The figures of the SB III device in the paper published by Putzier et al clearly show a positioning of the prostheses which are too anterior. McAfee et al [11] demonstrated a statistical correlation between prosthesis positioning and clinical outcomes at 2 years. Patients with poor implant placement had statistically worse clinical outcomes than patients with optimal placement.…”
mentioning
confidence: 98%